Tropical Pacific SST and ITCZ biases in climate models : double trouble for future rainfall projections? - Samanta, Dhrubajyoti (2019)
The double Intertropical Convergence Zone bias remains a persistent problem in coupled general circulation model simulations. Due to the strong sea surface temperature (SST)‐convection relationship in the tropics, precipitation biases are sensitive to background SST. Using historical simulations of 24 coupled general circulation models and an atmospheric general circulation model, we show that cold equatorial SST biases at least exacerbate double Intertropical Convergence Zone biases in the Pacific. A linear regression model is used to demonstrate that improved predictability of precipitation trends is possible with such model‐dependent information as mean‐state SST biases accompanying projected SST trends. These results provide a better understanding of the root of the double Intertropical Convergence Zone bias and a possible path to reduced uncertainty in future tropical precipitation trends.